Music Images in Portuguese and Portuguese-Spanish Painting in Portugal: Sources and Models Used in Painting Workshops - Duarte, Sónia (Eikón / Imago, 2016)
The hard work of surveying and studying the national dissemination of hundreds of music images in fifteenth and sixteenth century in Portuguese altarpieces, and others works with connections to Portugal, not only in living and record paintings but also those that little or nothing were written, allowed me to bring together a corpus of over eighty paintings, including a Nativity assigned to royal painter Gregorio Lopes, whose location was rediscovered in November 2010. What information do the images of Portuguese Renaissance paintings that were collected and analyzed in situ bring us? Which musical instruments are represented there? Which are the sources used to represent the musical aspects on paintings? Are these representations of daily musical life?